Pengintegrasian Maqashid Syariah dalam Strategi Pariwisata Halal: Etika Keagamaan, Hak Konsumen, dan Kerangka Hukum dalam Studi Kasus Lombok - Fitry Primadona; Marwata; Fakhry Fadhil (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study explores the strategic development of halal tourism marketing in Lombok by applying an integrated quantitative and religious-ethical approach. Using Structural Equation Modeling (SEM) and Importance-Performance Map Analysis (IPMA), this research identifies key drivers influencing Muslim tourists’ loyalty. The findings highlight that perceived value occupies the most critical position in the IPMA quadrant marked by the highest importance score (0.310) but relatively low performance (56.410). This gap reveals a strategic urgency to enhance the spiritual and emotional value embedded in halal tourism services. The study emphasizes that improving perceived value must go beyond technical compliance, aligning with core Islamic ethical principles such as maqashid shariah (protection of religion, life, wealth, intellect, and dignity) and muamalah (transparency, fairness, and honesty in transactions). Regulatory frameworks like Indonesia’s Halal Product Assurance Law further reinforce the legal obligation to uphold Muslim consumer rights in the public tourism sector. By embedding faith-based values into service design and marketing strategies, this paper argues for a model of halal tourism that integrates religious freedom, consumer protection, and social transformation. Lombok can serve as a benchmark destination that not only meets procedural halal standards but also fosters deeper spiritual satisfaction and inclusive service justice in a pluralistic society.